Assessment of dietary nitrate supplementation: prevalence of use, knowledge, attitudes and beliefs among active Australians - McMahon, Nicholas F.; Brooker, Paige G.; Pavey, Toby; Leveritt, Michael D. (Frontiers in Nutrition, 2023)
Introduction Use of nitrate as a dietary supplement has gained popularity among athletes and recreationally active individuals to enhance exercise performance. However, the prevalence and patterns of use, and knowledge of nitrate as a dietary supplement are unknown. Methods Individuals (≥16y) completed a 42-item online questionnaire to collect (i) sociodemographic information; (ii) participation in activity and sport; (iii) nitrate supplementation use and reasons; (iv) attitudes and beliefs regarding information sources and the safety of nitrate as a dietary supplement; and (v) knowledge of dietary nitrate supplements. Results In total, 1,404 active adults (66% female) took part in the study. Only about one in 10 respondents (11.9%) reported they had consumed dietary nitrate (“users”) in the past, most commonly as beetroot juice (31.3%). Over two-thirds (69.4%) of users could not correctly identify the correct timing of intake relative to performance time to best improve exercise performance, and most users (82.3%) were unsure of the contraindications to oral consumption of dietary nitrate supplements. Only 3.9% of users experienced adverse effects after ingesting dietary nitrate supplements. Among non-users, the most common reasons respondents selected for not using dietary nitrate supplements were “I do not think I need to” (70.2%) and “I have never thought about it” (69.2%). Discussion There is evidence to support the efficacy of dietary nitrate intake in improving exercise performance. However, findings from this study suggest dietary nitrate is under-utilized. Educational messages that target dietary nitrate consumption should be targeted toward nutritionists, coaches, and exercise physiologists to bridge the gap between knowledge-to-practice.